The European Higher Education Area: Between Critical Reflections and Future Policies - Curaj, Adrian; Matei, Liviu; Pricopie, Remus; Salmi, Jamil; Scott, Peter (Springer Nature, 2015)
Higher Education; Educational Policy and Politics; International and Comparative Education